Latex agglutination for rapid detection of Pseudomonas pseudomallei antigen in urine of patients with melioidosis. - Smith, M D (1995)
A latex agglutination test for the detection of Pseudomonas pseudomallei antigen in urine was evaluated for the rapid diagnosis of melioidosis. With unconcentrated urine, antigen was detected in only 18% of patients with melioidosis overall. However, when urine was concentrated 100-fold, antigen was detected in 47% overall and in 67% of patients with septicaemia or disseminated infection, in whom a rapid diagnosis is most important. The specificity of the test was 100%. These results compared favourably with an enzyme immunoassay. This latex agglutination test is a simple, rapid and highly specific method of diagnosing melioidosis, and will be particularly useful in areas with limited laboratory facilities.